Inverse Relationship between V˙O2max and Gross Efficiency - Hopker, J.; Coleman, D.; Jobson, S. A.; Passfield, L. (International Journal of Sports Medicine, 2012)
The aim of this study was to identify if an inverse relationship exists between Gross Efficiency (GE) and V˙O2max in trained cyclists. In Experiment 1, 14 trained cyclist’s GE and V˙O2max were recorded at 5 different phases of a cycling ‘self-coached’ season using an incremental laboratory test. In Experiment 2, 29 trained cyclists undertook 12 weeks of training in one of 2 randomly allocated groups (A and B). Over the first 6 weeks Group A was prescribed specific high-intensity training sessions, whilst Group B were restricted in the amount of intensive work they could conduct. In the second 6-week period, both groups were allowed to conduct high intensity training. Results of both experiments in this study demonstrate training related increases in GE, but not V˙O2max. A significant inverse within-subject correlation was evident in experiment 1 between GE and V˙O2max across the training season (r= − 0.32; P<0.05). In experiment 2, a significant inverse within-subject correlation was found between changes in GE and V˙O2max in Group A over the first 6 weeks of training (r= − 0.78; P<0.01). Resultantly, a training related inverse relationship between GE and V˙O2max is evident in these groups of trained cyclists.
Keywords: training; aerobic capacity; power output; performance